Structural Preferences and Vibrational Analysis of 2-Hydroxy-2-methyl-1-phenylpropan-1-one: A Computational and Infrared Spectroscopic Research. (29th May 2013) - Belaidi, O.; Bouchaour, T.; Maschke, U.
Abstract : The Fourier transform infrared (FTIR) spectrum of 2-hydroxy-2-methyl-1-phenylpropan-1-one has been measured in the region 4000–700 c m - 1 . The most stable conformation of title molecule was found after a careful potential energy surfaces study. The molecular geometry, vibrational frequencies, and infrared intensities have been calculated by using ab initio HF and density functional theory calculation B3LYP with 6-311+G * * basis set. Scaled frequencies and potential energy distribution were calculated for band assignment. We found an excellent agreement between the experimental and the simulated spectra. Energy gap between HOMO and LUMO explains the eventual charge transfer interactions taking place within the molecule.